A Retrospective Study of Verruca - Fadila, Arisia; Zulkarnain, Iskandar; Listiawan, M. Yulianto; Hidayati, Afif Nurul; Sawitri, Sawitri; Indramaya, Diah; Utomo, Budi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Verruca (non genital warts) is a quite common public health problem caused by viral infection of low risk Human Papilloma Virus (HPV) types, risking patients of all backgrounds. There is still no ideal treatment for verruca with little knowledge regarding the effectiveness of the available therapies, which results in the lack of therapeutic standard for patients. Purpose: To evaluate the incidence, management, and effectiveness of verruca treatment. Methods: This was a descriptive, retrospective study with a cross-sectional design.  All patients diagnosed with verruca in Tumor and Skin Surgery Division of the Dermatology and Venereology Outpatient Unit at Dr. Soetomo General Academic Hospital Surabaya between January 2016 and December 2020 were included in the study. Result: The results of this study obtained a total of 113 verruca patients, consisting of 61 (53.98%) male patients and 52 (46.01%) female patients, mostly aged 20-60 years old (45 patients [39.82%]). The upper extremity was the most common location where the lesion was found (39 patients [34.5%]). Electrosurgery was the most performed method (38 patients [33.6%]). Thirty-one patients who were treated and returned to the clinic at least once during the month were evaluated for the resolution of the lesion after undergoing therapy. Among 31 patients, resolution was reported in 35.5% of cases. Conclusion: Verruca is a common condition in general practice with many treatment options available yet often neglected. Knowing the available evidence for efficacy of those treatments is critical for dermatologist when considering treatment and educate patients.